Behavioral Epiphenomena Revisited: Reply to Skok and Škorjanc. (17th June 2014) - Hudson, Robyn; Hauber, M.
Abstract In a recent article in this journal, Ethology, 2014 present arguments as to why fighting in piglets during suckling may not be an epiphenomenon as we had previously suggested Ethology, 119, 2013, 353 and provide several alternative explanations. Although the new information Skok and Škorjanc bring to this debate is carefully considered and important, I argue here that it is not sufficient to counter our original claim that fighting among piglets (and kittens) during suckling may be an epiphenomenon, a largely inconsequential by‐product, of developmental processes anticipating the use of these behaviors and associated anatomical structures in later functional contexts. However, the points Skok and Škorjanc raise contribute importantly to identifying areas where further information and experimental work are needed to resolve this and related behavioral issues. I therefore conclude that this debate, independent of any particular final outcome, constructively points to the general difficulty and need for caution in interpreting behavior in seemingly 'obvious' functional terms, and particularly during development.